MiRNA Expression in Long-Distance Runners with Musculoskeletal Pain: Implications for Pain Pathophysiology - Maria Rosaria Tumolo; Antonella Bodini; Francesco Bagordo; Carlo Giacomo Leo; Pierpaolo Mincarone; Elisabetta De Matteis; Saverio Sabina; Tiziana Grassi; Egeria Scoditti (Biomedicines)
Background: miRNAs are short, non-coding RNAs whose deregulation has been shown in painful processes, including musculoskeletal pain. This condition, which causes disability, impacts quality of life, and contributes to substantial healthcare costs, is also a critical issue in sports. In this case-control study, we evaluated the expression of four miRNAs involved in inflammation in runners with musculoskeletal pain and elucidated their functions and pathophysiological implications. Methods: A total of 17 runners with musculoskeletal pain and 17 age- and sex-matched runners without pain participated in this study. The levels of the miRNAs were evaluated by qRT-PCR. Bioinformatic tools were employed to identify the target genes and biological processes regulated by these miRNAs. Results: Compared to the controls, the runners with musculoskeletal pain exhibited significantly higher plasma levels of miR-133b (p = 0.02), miR-155-5p (p = 0.003) and let-7a-5p (p = 0.02). Multivariable regression analysis indicated that these three miRNAs exhibit a positive correlation (p < 0.05) with the presence of musculoskeletal pain, adjusted for age. Bioinformatic analysis suggested that the miRNAs hub genes are involved in regulatory processes, neuroinflammatory pathways, and human diseases that are associated with pain pathology. Conclusions: These results enhance our understanding of the potential role of miR-133b, miR-155-5p and let-7a-5p in pain-associated biological processes. The miRNA-mediated negative regulation of genes identified could explain the inflammatory and tissue repair processes in this population. Further studies are needed to confirm and validate the role of these miRNAs in painful conditions, especially considering the significant public health implications of managing inflammatory pain in sports.